The effect of financial literacy and social media on micro capital through financial technology in the creative industry sector in East Java - Maria Widyastuti; Y. Budi Hermanto (Cogent Economics & Finance, 2022)
This study aimed to examine the effect of financial Literacy and social Media on micro capital through financial technology. This type of research is explanatory/associative, accompanied by hypothesis testing. The unit of analysis of this research is the Creative Industry Sector in East Java, with a population of 376 creative industries. The number of samples is 65 SMEs using the stratified random sampling method. The results of this study prove that financial literacy has a positive and significant effect on financial technology, social media has a significant effect on financial technology, financial literacy has a positive and significant effect on micro capital, social media has a significant effect on micro capital, and financial technology has a significant effect on micro capital.
Keywords: 330; financial literacy; social media; financial technology; micro capital